Obraz społeczeństwa i prowincji angielskiej za panowania Jerzego III w świetle „Listów wybranych” Jane Austen - Domarańczyk, Daria (Zeszyty Wiejskie, 2013)
The essay presents the profile of one of the most famous British writers – Jane Austen (1775–1817) and her thoughts on provincial life. The author of the "Pride and Prejudice" was particularly interested in the aspect of social relations and traditions. As the result, the writer created novels containing perfectly presented stories. The part of the Austen’s heritage are also her letters from 1796–1817. They are a very precious source of the studies on a British society during the reign of King George III. The letters were addressed mainly to a family and friends of the writer. They contain descriptions of nature, balls, trips to Bath and characteristic for the province gossips.